A influ??ncia da predisposi????o para relacionamentos rom??nticos de curto e de longo prazo na prefer??ncia por servi??os de maior risco - Vils, Leonardo (2015)
Two experiments based on principles of Darwin??s Sexual Selection and assumptions of Evolutionary Psychology, evaluate the tendency to conspicuous display of men and women in romantic stimulus conditions. The first experiment, 2x2 between subjects, indicates that men and women tend to a larger conspicuous display by choosing more risky sports activities, under romantic motives of short-term than long-term. As part of this propensity for exhibitionism, the second experiment, 4x2 between subjects, indicates that men and women, stimulated by short-term romantic motives, show a preference for differentiation messages when promoting services, showing an increase of competitiveness in the search for a casual partner than for the search for a lasting relationship. This study contributes to the understanding of consumer behavior under emotional stimuli of the same positive valence, and it relationship with different choices motivated by interest in short and long term relationships.